Bibliometric Analysis from the Perspective of a Croatian Tourism Journal - Tokić, Ksenija; Tokić, Ivo (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
Since the production of scientific journals in the field of tourism has been growing significantly in the last ten years, bibliometric analysis can be an important and useful tool for the evaluation of the productivity of scientists and scientific institutions, but also for the evaluation of scientific publications. It is gaining importance because bibliometric indicators are increasingly used as a benchmark for the granting of financial resources to institutions, researchers, journals, etc. Based on the results of research, in this paper the bibliometric analysis of the journal Tourism is presented.  The aim of the paper is to accentuate, on the example of the most important Croatian scientific tourism journal, the (not)appropriateness of the uncritical application of evaluation criteria designed for Anglo-Saxon environment in the context of a small academic community that uses a different language and can count on a modest financial support.